Determining factor for the hospitalization of neonates in the Neonatal Intensive Care Unit in Manaus - da Silva Medeiros, Ana Carolina; Ferreira dos Santos, Renata (O Mundo da Saúde, 2018)
Factors prior to conception directly influence the appearance of complications at birth. The objective of this study was to investigate the aspects that led to the hospitalization of neonates in the Neonatal Intensive Care Unit (NICU). This is a cross-sectional quantitative study. The reference population were infants hospitalized in NICUs and their mothers, hospitalized in three maternity hospitals in the city of Manaus. A higher prevalence of neonatal hospitalization was observed, with mothers only having incomplete / complete secondary education (40.2% n = 45), drug users such as Merla / mel (85.7% p-value = 2.30E -06) and monthly income ranging from 1 to 3 minimum wages (42%, n = 47). It is concluded that demographic, behavioral maternal factors and prenatal quality are determinants for the health conditions of the neonate, so that they enter the intensive care unit.